Peranan Muhammadiyah Bidang Pendidikan di Nagari Air Bangis Kabupaten Pasaman Barat - Murni, Asiam; Kaksim, Kaksim; Nurhuda, Ahmad (Pendidikan Sejarah, 2013)
ABSTRACT This thesis examines the role of Muhammadiyah in Nagari Air Bangis. Before the 1990s, very few people are capable of villages Air Bangis education. Villagers lack of knowledge about the Air Bangis education makes people especially Islamic education in running and embraced Islam is still tinged with mystical or superstitious. Muhammadiyah as an organization aimed at educating the nation are very concerned with what is experienced by the Nagari Air Bangis, With a hard struggle trying to advance education Muhammadiyah in nagari Air Bangis. It looks Muhammadiyah has been able to give birth to sons and daughters of the Air Bangis villages intelligent and virtuous noble character. Therefore this study aims to explain how the role of Muhammadiyah in Air Bangis. It can be concluded that the role of Muhammadiyah in Nagari Air Bangis immense. Schools and teaching that has been established by Muhammadiyah has been able to advance the Air Bangis villages, both in the fields of education, religion and social. Keywords: Role, Muhammadiyah, Education, Air Bangis